Morphological Diversity and Molecular RAPD Markers of Sugarcane Mutane (Saccharum officinarum L.) in Inundation Tolerance - Avivi, Sholeh; Suliswanto, Eko Nur; Restanto, Didik Pudji; Miswar, Miswar; Syamsunihar, Anang; Soeparjono, Sigit; Hartatik, Sri (AGRIVITA, Journal of Agricultural Science, 2019)
The study aimed to identify variations in morphological and molecular character of sugarcane mutants from the mutation of Ethyl Methane Sulphonate (EMS). It used 21 sugarcane mutants and two non-mutant PS865 plants as controls. The treatments with inundation were carried out on 1-17 mutants and non-mutants, while the treatments without inundation were carried out on 18-21 mutant plants and non-mutants. The tolerance characteristics base on the agronomic characters. The RAPD molecular character was observed to detect changes in genotypes and kinship relationships of the plants tested. The results showed that the characteristics of tolerance to the best inundation were found in mutants 1, mutants 3 and mutants 6 which were characterized by the root volume (cm3), fresh root weight (g), sucrose content and brix value (%). Mutant plants treated with inundation showed higher levels of sucrose and brix values. Whereas the control plants in fats, showed lower levels of sucrose and brix. Changes in sugarcane mutant genotypes from non-mutants based on RAPD markers ranged from 14.7 - 56.7 % which resulted in an average polymorphic band of 35.1 % from 37 DNA bands and produced four main groups based on dendrogram analysis.